Theoretical preliminaries of acoustics - Jarrett, Daniel P.; Habets, Emanuël; Naylor, Patrick A. (Theory and Applications of Spherical Microphone Array Processing, 2017)
In this chapter, we review some of the fundamentals of acoustics and introduce the spherical harmonic expansion of a sound field, which is the basis for the spherical harmonic processing framework used with spherical microphone arrays. This material provides an introduction to the key theory and equations that are required in the rest of the book.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Helmholtz Equation; Sound Field; Sound Pressure; Spherical Harmonic Expansion; Spherical Wave